2020
DOI: 10.3390/toxins12030195
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Apamin as a Bee Venom Component for Non-Neoplastic Disease

Abstract: Bee venom is a natural toxin produced by honeybees and plays an important role in defending bee colonies. Bee venom has several kinds of peptides, including melittin, apamin, adolapamine, and mast cell degranulation peptides. Apamin accounts for about 2%-3% dry weight of bee venom and is a peptide neurotoxin that contains 18 amino acid residues that are tightly crosslinked by two disulfide bonds. It is well known for its pharmacological functions, which irreversibly block Ca2+-activated K+ (SK) channels. Apami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 142 publications
(205 reference statements)
1
44
0
2
Order By: Relevance
“…These effects were attributed to inhibition of oxidative stress, apoptosis, and inflammation. Although previous studies have shown the beneficial effect of apamin against several inflammatory diseases [13][14][15][16][17][18], our study is the first to demonstrate the therapeutic action of apamin on LPS-induced AKI.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…These effects were attributed to inhibition of oxidative stress, apoptosis, and inflammation. Although previous studies have shown the beneficial effect of apamin against several inflammatory diseases [13][14][15][16][17][18], our study is the first to demonstrate the therapeutic action of apamin on LPS-induced AKI.…”
Section: Discussionmentioning
confidence: 65%
“…Much research has focused on the biological effects and clinical potential of bee venom and its main component, melittin [10][11][12]. However, accumulating evidence also has highlighted the importance of apamin as a drug candidate [13]. Apamin has been shown to exert anti-inflammatory, antioxidative, and antiapoptotic activities in animal models of several inflammatory diseases, including gouty arthritis [14], multiple sclerosis [15], chronic liver disease [16], acute pancreatitis [17], and atherosclerosis [18].…”
Section: Introductionmentioning
confidence: 99%
“…APM has long been known as a specifically selective blocker of SK2 channels [ 27 ]. Ca 2+ /calmodulin-dependent protein kinase II (CaMKII), one of the main downstream targets of Ca 2+ and CaM, is activated by Ca 2+ /CaM [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies have confirmed that APM is an anti-inflammatory and antiapoptotic agent that acts through vascular smooth muscle cell migration [ 22 ], biliary fibrosis and activation of hepatic stellate cells [ 23 ], TNFα/interferon (IFN)γ-induced keratinocytes [ 24 ], LPS/fat-induced atherosclerotic mice [ 25 ], and macrophage activation [ 26 ]. In addition, we recently investigated and reported the effect of APM on nonneoplastic disease [ 27 ]. Although studies have investigated the physiological function of APM, including anti-inflammatory and antiapoptotic functions, the effectiveness of APM related to LPS-induced microglial neuroinflammation has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, apamin can activate the inhibitory muscarinic M2 receptors in motor nerve terminals reducing the neuromuscular transmission [78]. Therefore, this capacity gives apamin the potential to be a part of the treatment of different CNS diseases [79].…”
Section: Apaminmentioning
confidence: 99%